ASSISTANCE IN THE PRODUCTION OF DALUMAN GREEN CIRCAU LEAVES (CYCLEABARBATA MIERS) AS A GASTRITIS THERAPY AT SMKN 1 BANYUPUTIH SITUBONDO - Gasim Soka , Burhanudin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
The aim of this community service is to increase knowledge regarding the herbal plant leaves of green grass jelly (Cyclea barbata miers) which can be used as a health drink for gastritis therapy. The public, especially students at SMKN 1 Banyuputih, know how to process Cyclea barbata miers green grass jelly as a health drink for gastritis therapy. The community service method used is socialization or delivery of material. After delivering the material, a question and answer session is held and a questionnaire is filled out to see the beneficial impact of the activities carried out. The results of the service obtained were that there was an increase in respondents' knowledge after listening to the speaker's explanation, respondents stated that they knew daluman leaves or grass jelly leaves after delivering the material. Respondents stated that the material presented was clear. Respondents stated that the material and practices presented were in accordance with the obstacles experienced by SMKN 1 Banyuputih students. Respondents stated that they had the opportunity to ask questions and express opinions. Respondents stated that the activities provided benefits to participants.